FINE NEEDLE ASPIRATION CYTOLOGY OF SOFT TISSUE LESIONS- A STUDY IN A TERTIARY CARE CENTRE (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Soft tissue lesions are challenging for the cytopathologist due to their biological heterogeneity and broad and overlapping morphological features.  FNAC is used as a primary diagnostic tool in the diagnosis of soft tissue lesions. FNAC is minimally invasive technique, relatively cheap cost, rapid, simple, and safe with fair specificity and sensitivity for the diagnosis of new cases and in differentiating benign from malignant cases. Material and Methods: The current study employed a “prospective- retrospective” research design with a total duration of 02 years. The retrospective phase covers the period from 30th April 2024 to 1st May 2023 and prospective phase spans from 1st May 2024 to 30th April 2025 in the Cytology section of Department of Pathology, GMC Jammu.  Diagnosis was confirmed by studying MGG and PAP-stained slides. Results: Out of the total 659 cases studied, 621 cases (94.23%) were diagnosed as benign soft tissue lesions and 38 cases (5.77%) were diagnosed as malignant soft tissue tumor based on cytomorphological evaluation. The male-to-female ratio was 1.12:1. The upper back was the most common anatomical site of involvement. The age group 21-30 most commonly involved showing predilection towards younger patients. Conclusion: Though Histopathology remains the gold standard, particularly for subtyping and grading, supported by ancillary techniques like immunohistochemistry (IHC) and molecular assays. FNAC can definitely be used as an initial screening tool in diagnosis of soft tissue lesions.